Worklife Balance Among Female Nurses In Private Sectors - Nur Atiqah Nabilah, Azhar (Universiti Malaysia Sarawak (UNIMAS), 2020)
Work-life balance is often an issue for working women such as nurses, as well as shouldering responsibilities as a mother. This study examines the work life balance among female nurses in private hospitals. This study was conducted to identify the balance of working life among female nurses and also understand the factors that contribute to the balance of working life among female nurses in Private Sector Hospitals. The study was conducted in a private hospital, with the method of interviewing (5) nurses as informants. The informant was also selected through a convenience sampling method. The data obtained through the interview will be analyzed through the transcription of the analysis data. The findings of this study have proven that nurses in private hospitals are able to balance working life in their lives. But they are facing a shortage of staff at the hospital. This study also showcases the factors that help them to achieve a working life balance. Implications and suggestions for improving the working life balance of nurses are also emphasized in this study